1988
DOI: 10.1002/aja.1001830404
|View full text |Cite
|
Sign up to set email alerts
|

Dentin resorption mediated by odontoclasts in physiological root resorption of human deciduous teeth

Abstract: Extracted human deciduous teeth undergoing physiological root resorption were fixed with a mixture of formaldehyde and glutaraldehyde and processed for scanning (SEM) and analytical transmission electron microscopy, as well as acid trimetaphosphatase cytochemistry. The granulated tissues, which are rich in multinucleated odontoclasts and capillary vessels, formed various resorption lacunae on the resorbing dentin surfaces. SEM observations of dentin surfaces treated with sodium hypochlorite revealed two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
6

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 29 publications
(43 reference statements)
2
33
0
6
Order By: Relevance
“…It is interesting that the whole tooth bud of the minke whale is physiologically absorbed before birth, whereas only the root of the deciduous teeth of other mammalian species is partly absorbed after birth [8,9]. Degeneration of the deciduous teeth in diphyodont animals characterized by resorption of the dental root might be promoted by the physical force of the developing permanent teeth [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that the whole tooth bud of the minke whale is physiologically absorbed before birth, whereas only the root of the deciduous teeth of other mammalian species is partly absorbed after birth [8,9]. Degeneration of the deciduous teeth in diphyodont animals characterized by resorption of the dental root might be promoted by the physical force of the developing permanent teeth [10].…”
Section: Discussionmentioning
confidence: 99%
“…Namely, exposure of collagen fibrils at the resorbing cementum and dentine surfaces, dissolution of the peritubular matrix around dentinal tubules in the resorbing dentine surfaces, and dissolution of the enamel rods and/or their peripheral areas at the resorbing enamel surfaces were clearly demonstrated (Sasaki et al, 1988a;Matsuda, 1992). Therefore, it is apparent that decalcification of the matrices occurs at the resorbing surfaces of these dental hard tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Past scanning electron microscopic observations have indicated that decalcification of the root dentine surfaces in the resorption lacunae preceded the removal of the organic materials Jones et al, 1984;Sasaki et al, 1988aSasaki et al, , 1990bMatsuda, 1992). Namely, exposure of collagen fibrils at the resorbing cementum and dentine surfaces, dissolution of the peritubular matrix around dentinal tubules in the resorbing dentine surfaces, and dissolution of the enamel rods and/or their peripheral areas at the resorbing enamel surfaces were clearly demonstrated (Sasaki et al, 1988a;Matsuda, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki et al (1988) suggested that odontoclastic resorption of the tooth root proceeds in a manner similar to that in osteoclastic bone resorption. In contrast, Gonzales et al (2009) found that like osteoclasts, odontoclasts could express CK during orthodontic tooth movements.…”
Section: Introductionmentioning
confidence: 99%